Functional polymorphism -31C/G in the promoter of BIRC5 gene and risk of nasopharyngeal carcinoma among chinese. - Fuchao Ma; Hongxing Zhang; Yun Zhai; Wenfeng Huang; Chang Zhao; Shengqiu Ou; Hong Zhou; Wenzhao Yuan; Zhifu Wang; Hongxue Wang; Wei Yue; Lixia Yu; et al. (PLoS ONE, 2011)
BACKGROUND:Baculoviral inhibitor of apoptosis repeat-containing 5 (BIRC5, also called as survivin) is a member of the inhibitor of apoptosis protein (IAP) family, which plays an important role in the occurrence and progression of cancer. Recently, a polymorphism in the promoter of BIRC5, -31C/G (rs9904341), was shown to influence BIRC5 expression. METHODS:We examined whether the -31C/G was related to the risk of developing nasopharyngeal carcinoma (NPC) in a case-control population from Guangxi province in southern China, which consists of 855 patients with NPC and 1036 controls. This polymorphism was genotyped by TaqMan assay. The genetic associations with the occurrence and progression of NPC were estimated by logistic regression. RESULTS:We observed a statistically significant increased occurrence of NPC associated with the CC genotype (odds ratio [OR], 1.40; 95% confidence interval [CI], 1.13-1.73; P=0.0020) compared with the genotypes containing G allele (CG + GG genotype). However, no significant association was observed for the -31C/G with the severity of NPC (as measured by tumor-node-metastasis staging system). CONCLUSION:Our findings suggest that the functional polymorphism -31C/G in the promoter of BIRC5 gene may play a role in mediating the susceptibility to NPC among Chinese.